Divergent roles of nitrergic and prostanoid pathways in chronic joint inflammation. Issue 12 (16th November 2004) - Day, S M; Lockhart, J C; Ferrell, W R; McLean, J S
Abstract : Background: Nitrergic and prostanoid pathways have both been implicated in inflammatory processes. Objective: To investigate their respective contributions in a rat model of chronic arthritis. Methods: Male Wistar rats (n = 4–6/group) received either an intra-articular injection of 2% carrageenan/4% kaolin (C/K) or intra- and periarticular injections of Freund's complete adjuvant (FCA; 10 mg/ml M tuberculosis ). Joint diameter, urinary nitric oxide metabolites (NOx ), and prostaglandin E2 (PGE2 ) levels were measured as indices of the inflammatory process. A prophylactic and therapeutic (day 5) dose ranging study of an inducible nitric oxide synthase inhibitor, l - N -(1-iminoethyl)-lysine (l -NIL), and a cyclo-oxygenase-2 (COX-2) inhibitor, SC-236, was performed with the drugs given subcutaneously. Submaximal doses were identified and used for combination studies. Appropriate vehicle controls were included. Results: l -NIL and SC-236 dose dependently inhibited C/K induced acute joint swelling, the magnitude being greatest when they were given in combination. Both prophylactic and therapeutic administration of SC-236 in the FCA induced model of chronic arthritis produced a dose dependent reduction in all the measures assessed. However, although l -NIL demonstrated similar dose dependent inhibition of urinary NOx and PGE2 levels, joint swelling was significantly exacerbated in this model. Co-administration of the inhibitors nullified the benefits of SC-236. Conclusion: Whereas COX-2 derived prostaglandins are proinflammatory in both acute and chronic joint inflammation, NO seems to have divergent roles, being anti-inflammatory in chronic and proinflammatory in acute joint inflammation.